PENERAPAN PERHITUNGAN HARGA POKOK PRODUKSI SEBAGAI UPAYA UMKM MEMAKSIMALKAN LABA - Ni Luh De Erik Trisnawati; Dewa Ayu Putu Yulia Ardiani; Komang Ayu Parwati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
When it comes to micro, small and medium enterprises (MSMEs), profit maximization and business continuity are often secondary concerns. Businesses usually face challenges when trying to price their goods because it is not easy to know how much it costs to make them. In addition to affecting the profits generated, wrong pricing decisions can put a company in danger of losing money and ultimately lead to its downfall. Many small and medium enterprises (SMEs) in Singapore face this problem. When calculating production costs, business actors often only take into account the costs of raw materials. It does not take into account additional costs that should be part of the production cost calculation, such as direct labor costs and factory overhead costs. This service activity aims to provide education to MSMEs in determining production costs in response to this situation. The impact of errors in determining production costs on the amount of profit obtained was also explained to MSME players. The findings of this service activity provide enlightenment on how MSMEs should set the prices of their merchandise. A key component of good company management is the ability to make choices based on accurate financial data.